“PICC”ing Patients with Chronic Kidney Disease - Yaqub, Sonia; Raheel, Muhammad; Razzaque, Abdul; Naeem, Zarghoona (Pakistan Journal of Kidney Diseases, 2021)
Patients with Chronic Kidney Disease (CKD) eventually progress to kidney failure and require dialysis. These patients often present withcomplicated medical conditions requiring intravenous medical therapies; however, at the same time it is of paramount importance to maintain integrity of veins to provide a future hemodialysis (HD) vascular access. Peripherally inserted central catheters (PICC) are used for patients requiring prolonged intravenous medications. PICC lines may cause local trauma and influence the future vascular access creation. The aim of this study was to determine the frequency and indications of PICC lines use in hospitalized patients at a tertiary care hospital. Patients and Methods: All patients were retrospectively reviewed over 2 months for PICC line placement, indications and their estimated glomerular filtration rate. Results: Total of 147 PICC lines were placed and 20% of such patients had an eGFR <60 ml/min with possible need of vascular access in future. Conclusion: Placement of PICC lines in CKD patients is common and should be discouraged due to the possible need in the future for vascular access.